Saeculum obscurum - der epigraphische Befund (ca. 890-1000) - Zöller, Wolf (Quellen und Forschungen aus italienischen Archiven und Bibliotheken, 2019)
This article investigates the epigraphic remains of early medieval Rome, focusing on topological and material aspects of tenth-century inscriptions commissioned by the city’s bishops and leading nobles. Despite large collections of Roman inscriptions, epigraphic surveys of the period ca. 890-1000 are conspicuously lacking, reflecting the reputation of an era widely known as the Dark Ages. However, the epigraphic evidence provides a deeper understanding of the material language and communicative mechanisms deployed for the representation of power within the urban fabric of Rome. Case studies on papal epitaphs in St. Peter’s and votive inscriptions in the restored Lateran basilica demonstrate how inscribed artefacts were carefully integrated into much frequented architectural and liturgical settings. Sophisticated epigraphic configurations allowed for an enhanced interaction between inscriptions and their immediate material and social environment, not least during the Formosian controversy and the emotionally charged reconstruction of the cathedral church, when rival popes quarrelled over control of the highly contested urban space of Rome. Similarly, local aristocrats utilized inscribed marble slabs of considerable proportions to monumentalize their dominant political position. Above all, the famous Teofilatti penetrated the patriarchal basilicas of S. Lorenzo fuori le mura and S. Maria Maggiore for the sake of their family memoria, while their building inscriptions underscored their attempts to permanently reshape the Roman cityscape.
Gesehen am 04.02.2020